Managing negative linear compressibility and thermal expansion through steric hindrance: a case study of 1,2-bis(4′-pyridyl)ethane cocrystals - Ewa Patyk-Kaźmierczak; Kornelia Szymańska; Michał Kaźmierczak (IUCrJ, 2025)
Multicomponent crystals have great scientific potential because of their amenability to crystal engineering in terms of composition and structure, and hence their properties can be easily modified. More and more research areas are employing the design of multicomponent materials to improve the known or induce novel physicochemical properties of crystals, and recently they have been explored as materials with abnormal pressure behaviour. The cocrystal of 1,2-bis(4′-pyridyl)ethane and fumaric acid (ETYFUM) exhibits a negative linear compressibility behaviour comparable to that of framework and metal-containing materials, but overcomes many of their deficiencies restricting their use. Herein ETYFUM was investigated at low temperature to reveal negative thermal expansion behaviour. Additionally, a cocrystal isostructural with ETYFUM, based on 1,2-bis(4′-pyridyl)ethane and succinic acid (ETYSUC), was exposed to high pressure and low temperature, showing that its behaviour is similar in nature to that of ETYFUM, but significantly differs in the magnitude of both effects. It was revealed that the minor structural difference between the acid molecules does not significantly affect the packing under ambient conditions, but has far-reaching consequences when it comes to the deformation of the structure when exposed to external stimuli.